Foundations of Islamic Law: The Qur'an, Sunnah, Ijma', and Qiyas in the Study of Usul al-Fiqh - Nur Amelia Putri; Amirah Faradisa; Jundah Siti Nusrotul Milah; Galena Astuty Sri Sulastri; Sandra Diniarti; Bunga Ayunda Cindy Claudia; Taufiq Kurniawan (Penerbit Yayasan Daarul Huda Kruengmane, 2026)
Every adult Muslim carries a spiritual responsibility to organize and conduct life according to the principles of Islamic law. In the discipline of Usul Fiqh, Islamic legal foundations are primarily derived from four mutually acknowledged sources: the Qur'an, Sunnah, Ijma', and Qiyas. The Qur'an and Sunnah function as the principal normative references that contain legal principles, ethical values, and rulings, both explicitly stated and implicitly indicated. However, the development of time and the emergence of new contemporary issues that are not directly addressed in the Qur'an or Hadith require an adaptive legal methodology. In this regard, Ijma' and Qiyas play a crucial methodological role in shaping Islamic legal development. Ijma' refers to the consensus of qualified scholars after the passing of Prophet Muhammad (peace be upon him) in determining legal rulings on specific matters, thereby providing collective legitimacy. Meanwhile, Qiyas operates through analogical reasoning by relating new cases to established textual rulings based on shared effective legal causes (‘illat). Through these four foundations, Islamic law remains dynamic, applicable, and capable of addressing societal needs across different periods and contexts.